Comparison of skin color between two Asian populations: according to latitude and UV exposure. (8th January 2015) - Cho, Changhui; Ruan, Peiyi; Lee, Eunyoung; Ha, Jaehyoun
Summary Background Skin color varies among ethnic groups on accounts of genetic background. Within an ethnic group, skin color may also vary according to geographical environments and sun exposure habits. While many reports address skin color differences between ethnic groups, few have compared skin color within as ethnic group. Aims To compare skin color characteristics according to differences in latitude including UV exposure between two Asian populations (Korean and Cantonese [Chinese]). Method We included 461 healthy female subjects: 317 Korean (age 42.3 ± 7.16) and 144 Cantonese (age 41.5 ± 11.2). Skin phototypes were classified according to the Fitzpatrick classification, and back skin color measured using the Minolta colorimeter. We evaluated the lightness (L*), yellowish (b*) value, individual typology angle (ITA°), and minimal erythema dose (MED). Results Fitzpatrick phototype ratios were similar in Korean (II: 19.9%, III: 78.9%) and Cantonese (II: 27.1%, III: 72.9%). However, the L* (68.47 ± 2.66 vs. 66.44 ± 2.47), ITA° (41.80 ± 5.51 vs. 40.20 ± 5.79), and b* (20.56 ± 1.71 vs. 19.28 ± 1.97) were significantly higher in Korean than in Cantonese. Korean had a significant lower MED than Cantonese (22.33 ± 2.89 vs. 23.38 ± 6.04). Conclusions Subjective phototype self‐assessment showed similar results in Korean and Cantonese. However, objective skin color parameters differed between the two populations. Koreans, who live at a higher latitude and get relatively little sun exposure, have lighter skin color than the Cantonese and burn easily upon UV exposure.